2020
DOI: 10.1002/nbm.4285
|View full text |Cite
|
Sign up to set email alerts
|

Application of low‐rank approximation using truncated singular value decomposition for noise reduction in hyperpolarized 13C NMR spectroscopy

Abstract: Dissolution dynamic nuclear polarization allows in vivo studies of metabolic flux using 13 C-hyperpolarized tracers by enhancing signal intensity by up to four orders of magnitude. The T 1 for in vivo applications is typically in the range of 10-50 s for the different 13 C-enriched metabolic substrates; the exponential loss of polarization due to various relaxation mechanisms leads to a strong reduction of the signal-to-noise ratio (SNR). A common solution to the problem of low SNR is the accumulation/averagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…One commonly used class of denoising methods consists of low-rank denoising methods such as principal component analysis (PCA)-based denoising, with applications in, for example, diffusion imaging 25 and functional MRI, 26 as well as MRS and MRSI. 24,[27][28][29] A requirement for PCA-based denoising is that data can be transformed to a large signal matrix, which has homogeneous noise and high similarity of information, as expected for 3D MRSI of large organs such as the liver. It has been shown that PCAbased denoising yields an approximate SNR gain of 5 when applied to simulated 31 P MRSI data and an SNR gain of 3 for in vivo measured 31 P MRSI data of the upper legs.…”
Section: Introductionmentioning
confidence: 99%
“…One commonly used class of denoising methods consists of low-rank denoising methods such as principal component analysis (PCA)-based denoising, with applications in, for example, diffusion imaging 25 and functional MRI, 26 as well as MRS and MRSI. 24,[27][28][29] A requirement for PCA-based denoising is that data can be transformed to a large signal matrix, which has homogeneous noise and high similarity of information, as expected for 3D MRSI of large organs such as the liver. It has been shown that PCAbased denoising yields an approximate SNR gain of 5 when applied to simulated 31 P MRSI data and an SNR gain of 3 for in vivo measured 31 P MRSI data of the upper legs.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of apparent denoising are consistently achieved by denoising algorithms in MRS with additional encoding dimensions, 7 , 8 or MRSI. 1 , 9 , 10 However, it is not clear whether there is an overall reduction in uncertainty of final dynamic model parameters, 11 or metabolite concentrations (the typical output of MRSI).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of apparent denoising are consistently achieved by denoising algorithms in MRS with additional encoding dimensions (7,8), or MRSI (1,9,10). However, it is not clear whether there is an overall reduction in uncertainty of final dynamic model parameters (11), or metabolite concentrations (the typical output of MRSI).…”
Section: Introductionmentioning
confidence: 99%